ACTIVIDADES DE DANZA FOLKLÓRICA Y LAS HABILIDADES MOTRICES BÁSICAS EN LA CLASE DE EDUCACIÓN FÍSICA - FRANCO REBOLLEDO, MERCEDES DEL PILAR (2024)
The objective of this research is to analyze the relationship that exists between folk dance activities and basic motor skills in physical education class in 7th grade students. The methodology used had a quantitative cross-sectional, descriptive-correlational approach. , the study population was made up of 169 students from the Juan Montalvo educational unit, the sampling was intentional non-probabilistic, the sample selection criteria focus on boys and girls in 7th A of basic school at the school, the sample is comprised by 38 students, 20 male and 18 female, age 11 years, for the analysis of the data it was carried out through the frequency table and the application of the Pearson chi square test to establish if there is a highly significant relationship between folk dance activities and basic motor skills, the most relevant results were that there is a significant relationship between folk dance activities and basic motor skills in the physical education class with a p value of 0.014 for a level of significance of 0.05, this is evidenced by the fact that folk dance activities are closely related to postures, rhythm, flexibility, walking as well as jumping, including sensory perceptions that allow the development of motor skills.